Microlithiasis of the gallbladder: role of endoscopic ultrasonography in patients with idiopathic acute pancreatitis - Ardengh,José Celso (2010)
OBJECTIVES: Causes may be found in most cases of acute pancreatitis, however no etiology is found by clinical, biological and imaging investigations in 30% of these cases. Our objective was to evaluate results from endoscopic ultrasonography (EUS) for diagnosis of gallbladder microlithiasis in patients with unexplained (idiopathic) acute pancreatitis. METHODS: Thirty-six consecutive non-alcoholic patients with diagnoses of acute pancreatitis were studied over a five-year period. None of them showed signs of gallstones on transabdominal ultrasound or tomography. We performed EUS within one week of diagnosing acute pancreatitis. Diagnosis of gallbladder microlithiasis on EUS was based upon findings of hyperechoic signals of 0.5-3.0 mm, with or without acoustic shadowing. All patients (36 cases) underwent cholecystectomy, in accordance with indication from the attending physician or based upon EUS diagnosis. RESULTS: Twenty-seven patients (75%) had microlithiasis confirmed by histology and nine did not (25%). EUS findings were positive in twenty-five. Two patients had acute cholecystitis diagnosed at EUS that was confirmed by surgical and histological findings. In two patients, EUS showed cholesterolosis and pathological analysis disclosed stones not detected by EUS. EUS diagnosed microlithiasis in four cases not confirmed by surgical treatment. In our study, sensitivity, specificity and positive and negative predictive values to identify gallbladder microlithiasis (with 95% confidence interval) were 92.6% (74.2-98.7%), 55.6% (22.7-84.7%), 86.2% (67.4-95.5%) and 71.4% (30.3-94.9%), respectively. Overall EUS accuracy was 83.2%. CONCLUSIONS: EUS is a very reliable procedure to diagnose gallbladder microlithiasis and should be used for the management of patients with unexplained acute pancreatitis. This procedure should be part of advanced endoscopic evaluation.